(untitled) (American Journal of Islam and Society, 2004)
In this introduction to the large, unwieldy, and complex topic of Islamic historiography, the author has limited himself to historical works written in Arabic, primarily in the central Islamic lands, before 1500. This choice can be justified in that the field’s formative works written early on in Iraq, Iran, Egypt, and Syria and all in Arabic, served as models for historians writing later on in peripheral regions and in other languages. Nevertheless, it is a bow to convenience and necessity, given the vast amount of material involved. As a result, the Arabic historiography of North Africa, Sub-Saharan Africa, and other peripheral regions are largely ignored, as are the Turkish histories of the Ottoman Empire and the Persian histories of Iran, Central Asia, and India. Within these admitted and understandable limitations, the book provides an excellent thematic overview, while, at the same time, introducing the reader to some of the Islamic world’s most fascinating histories and historians. This book is divided into three parts, including ten chapters and a conclusion. A glossary, five plates of manuscript folios, three maps, two chronologies of prominent historians, and suggestions for further reading contribute to making this a useful and accessible text. In part 1, chapters 1-4, Robinson presents a tripartite typology of historical works: chronography, biography, and prosopography. These are ideal types, which serve as broad categories within which to classify a huge body of texts. Chronography refers to annals, works organized into year-by-year sections; biography refers to texts that treat the lives of famous or exemplary individuals; and prosopography refers primarily to biographical dictionaries, works in which biographical notices are devoted to large numbers of individuals who all belonged to a particular scholarly or professional group. All of these types of historical works, Robinson writes, had emerged by the ninth century and were consolidated by the early tenth century. The end of this formative period was characterized by large synthetic works, such as Abu Ja`far al-Tabari’s History of Messengers and Kings. In part because of such works, many earlier historical monographs, including the works of such historians as Abu Mikhnaf and al-Mada’ini, were abandoned by the tradition as unnecessary ...